Water at surfaces with tunable surface chemistries. (21st February 2018) - Sanders, Stephanie E; Vanselous, Heather; Petersen, Poul B
Abstract: Aqueous interfaces are ubiquitous in natural environments, spanning atmospheric, geological, oceanographic, and biological systems, as well as in technical applications, such as fuel cells and membrane filtration. Where liquid water terminates at a surface, an interfacial region is formed, which exhibits distinct properties from the bulk aqueous phase. The unique properties of water are governed by the hydrogen-bonded network. The chemical and physical properties of the surface dictate the boundary conditions of the bulk hydrogen-bonded network and thus the interfacial properties of the water and any molecules in that region. Understanding the properties of interfacial water requires systematically characterizing the structure and dynamics of interfacial water as a function of the surface chemistry. In this review, we focus on the use of experimental surface-specific spectroscopic methods to understand the properties of interfacial water as a function of surface chemistry. Investigations of the air–water interface, as well as efforts in tuning the properties of the air–water interface by adding solutes or surfactants, are briefly discussed. Buried aqueous interfaces can be accessed with careful selection of spectroscopic technique and sample configuration, further expanding the range of chemical environments that can be probed, including solid inorganic materials, polymers, and water immiscible liquids. Solid substrates can be finely tuned by functionalization with self-assembled monolayers, polymers, or biomolecules. These variables provide a platform for systematically tuning the chemical nature of the interface and examining the resulting water structure. Finally, time-resolved methods to probe the dynamics of interfacial water are briefly summarized before discussing the current status and future directions in studying the structure and dynamics of interfacial water.